Deterioration of sea sand roller compacted concrete used in island reef airport runway under salt spray. (7th March 2022) - Zhang, Huigui; Zhang, Wuman; Meng, Yanfei; Li, Honghe
Highlights: Sea sand RCC used in island reef is subjected to 400 salt spray cycles. The wear mass of sea sand RCC is increased by 27.9%. The compressive and the flexural strength of sea sand RCC is decreased by 32.3% and 14.8%. The fatigue impact resistance of sea sand RCC is decreased by 37.3%. Abstract: The river sand was replaced by untreated sea sand in roller compacted concrete (RCC) subjected to the salt spray cycles which was produced by 5% sodium sulfate solution. The relative elastic modulus, the mass loss in the wear resistance test, the fatigue impact resistance, the flexural and the compressive strength were investigated. The results show that the relative elastic modulus is decreased by 3.8% and 1.3%, the mass loss in the wear resistance test is increased by 27.9% and 11.9% when sea sand RCC and river sand RCC are subjected to 400 salt spray cycles. The compressive and the flexural strength of sea sand RCC with 400 salt spray cycles is decreased by 32.3%. and 14.8%, respectively. The fatigue impact resistance of sea sand RCC and river sand RCC is decreased by 37.3% and 21.2% when the salt spray cycles are raised from 100 cycles to 400 cycles.